The Albigensian Crusade - Sumption, Jonathan (London Faber & Faber, 1978)
In the twelfth century, Languedoc, in the far south, was among the most beautiful parts of France, far away from the world of the feudal north. However, it was in this rich region that a heresy of Eastern origin took hold, forcing the Catholic Church to confront a rival whose teachings questioned the foundations of Christian thought. These heretics, called Cathars, held a profoundly pessimistic view of the world that was based on the duality of all things, including good and evil: according to one heretic, "The one, the good God, made the invisible world, while the other, the evil God, made the visible one."Jonathan Sumption's acclaimed history examines the roots of this heresy as well as of the crusade the Church undertook in 1208 to stamp out the infidels, who ultimately were conquered by the Catholic armies. But this book does more than simply describe this terrible war; it reconstructs a lost world of great cultural richness, one that saw the creation in Languedoc of the troubadour tradition as well as the magnificent castles at Cabaret and Carcassonne.
Keywords: Middle Ages (500-1400); History; Catharism; Languedoc (France)